The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fpsyg.2021.699962
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetics and Psychological Effects of Fractal Based Design

Abstract: Highly prevalent in nature, fractal patterns possess self-similar components that repeat at varying size scales. The perceptual experience of human-made environments can be impacted with inclusion of these natural patterns. Previous work has demonstrated consistent trends in preference for and complexity estimates of fractal patterns. However, limited information has been gathered on the impact of other visual judgments. Here we examine the aesthetic and perceptual experience of fractal ‘global-forest’ designs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 33 publications
4
8
0
Order By: Relevance
“…Forest environment (Shinrin-yoku / forest bathing) reduces stress the study group led by Qing Li investigated the effect of Shinrin-yoku on the human immune system and confirmed that being in nature, where nature is rich in phytoncides, increases the number of NK cells that kill tumour cells. Being in nature is beneficial because of the negative ions found in nature, that provide energy and clearness of mind (Li 2019), as well as because of the natural patterns called fractals, which reduce mental fatigue and stress, while the lack of natural fractals in daily life can cause headaches (Robles, 2021).…”
Section: The Health Benefit Of Forest Bathingmentioning
confidence: 99%
“…Forest environment (Shinrin-yoku / forest bathing) reduces stress the study group led by Qing Li investigated the effect of Shinrin-yoku on the human immune system and confirmed that being in nature, where nature is rich in phytoncides, increases the number of NK cells that kill tumour cells. Being in nature is beneficial because of the negative ions found in nature, that provide energy and clearness of mind (Li 2019), as well as because of the natural patterns called fractals, which reduce mental fatigue and stress, while the lack of natural fractals in daily life can cause headaches (Robles, 2021).…”
Section: The Health Benefit Of Forest Bathingmentioning
confidence: 99%
“…Leder and Nadal (2014) indicated that some aesthetic experiences are explained by the perceptual features of the stimuli. Several perceptual attributes, related to low-level (e.g., contrast, color, and fractal pattern) or mid-level (e.g., symmetry and complexity) features, have been shown to affect judgments of preference both in artworks and stimuli in general (Grebenkina et al, 2018; Nadal et al, 2010; Robles et al, 2021; Stanischewski et al, 2020). People tend to prefer one stimulus to another when a perceptual attribute is modified (Braun & Doerschner, 2019; Nakauchi et al, 2022; Pecchinenda et al, 2014).…”
Section: Curvature Affects Preference For Paintings Viewed In Museumsmentioning
confidence: 99%
“…To account for possible effects of participant subgroups driving the overall observed trends, a two-step cluster analysis was performed (see Robles et al, 2021). In accordance with and described in Norušis (2012) hierarchical cluster analyses were first completed using Ward's method to separate individuals into groups using their appeal ratings for each level of pattern complexity.…”
Section: Appealmentioning
confidence: 99%
“…Objective pattern complexity results from variations in the relative coarse-to-fine pattern structure determined by internal pattern factors such as variations in recursion (number of repetitions across scales) and complexity of fractal dimension "D-value" (the rate of pattern shrinkage between repetitions to quantify the ratio of fine structure). Perceived pattern complexity also constrains broader pattern judgments (Abboushi et al, 2019;Robles et al, 2021). Selection of optimal fractal features expands beyond observed improvements to esthetic experiences of a given object, to facilitate viewer cognition and performance on a wide span of tasks (Juliani et al, 2016;Taylor et al, 2018;Abboushi et al, 2019;Roe et al, 2020;Spehar and Stevanov, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation